Juridical analysis of violence threats through electronic systems: Decision Study Number 82/PID.SUS/2021/PN.LWK - Iwan Setiawan; Tres Kumar; Graha Kusala; Rio Natanael Sitindaon; Muhlizar Muhlizar (Privietlab, 2022)
Rapid changes in society, the economy, and culture have resulted from the advancement of information and communication technology. Information technology is currently a two-edged sword, because, in addition to improving welfare, progress, and human civilization, it is also an effective means of committing illegal acts. The lack of human resources prepared to use information technology, both intellectually and psychologically, has made the complexity of information technology a tool that is easy to use as a criminal medium, or has influenced the birth of new things in everyday life. The approach method of reviewing the problem studied in terms of legal science and conducting an analysis of the legal norms and regulations that apply in laws and regulations based on primary, secondary, and tertiary legal materials is used in this study. to make conclusions based on the data collected during the study. The occurrence of criminal acts of threats of violence carried out through the electronic system, namely the short message service (SMS), is specifically influenced by psychological and sociological factors, and generally occurs as a result of the perpetrators' lack of legal awareness in social life. If the elements of criminal responsibility are met, criminal responsibility for the perpetrators of these crimes can be sought. The application of the law against perpetrators of criminal acts of threats of violence via short message services (SMS) was found to be in accordance with legal procedures based on trial facts in the study of the decisions examined. The defendant's actions, according to the panel of judges, settled the elements of Article 45 b Amendments to Law No. 11 of 2008 on Information and Electronic Transactions by Law No. 19 of 2016